The Tradition Of Grebeg Suro - Nurrokhim, Isma; Toyibatussalamah, Toyibatussalamah; Mahmud, Ali; Chelmi, Rahmatul (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2025)
This study examines the Grebeg Suro tradition in Menang Village, Kediri, as a multifaceted Javanese heritage that encompasses spiritual, social, and economic dimensions. The research aims to explore the tradition's role as a medium for social harmony, cultural education, and community empowerment. Utilizing a descriptive qualitative approach, data were collected through participant observation, documentation, and interviews with traditional leaders, village officials, and local residents. The findings indicate that Grebeg Suro facilitates intergenerational interaction and strengthens communal solidarity while serving as a vital mechanism for transferring local symbols and values to the younger generation. Furthermore, the tradition acts as a catalyst for community empowerment by stimulating the creative economy and local tourism through the involvement of MSMEs and performing arts. The study concludes that the revitalization of Grebeg Suro is essential for maintaining cultural relevance amidst modernization. By integrating social cohesion with economic independence, the tradition serves as a strategic instrument for sustainable socio-cultural development. Ultimately, Grebeg Suro transcends ritualistic ceremony, functioning as a foundational pillar for building a resilient and culturally grounded community.